Determining The Quality Assurance of Culinary Arts Graduates: The Mediating Role of Joint Commitment - Sinarsih, Wa Ode Sinarsih; Putu Sudira; Nur Wahyuni; Ika Wahyu Kusuma Wati (Jurnal Pendidikan dan Pengajaran, 2025)
This research is motivated by the problems surrounding the unoptimal quality assurance system for graduates in the field of culinary arts, which has an impact on the gap between graduate competencies and industry needs. This study explores the influence of transformational leadership and partnership management on the quality assurance of culinary arts graduates in vocational education, with the mediating role of joint commitment. This study is an ex-post facto study that uses a quantitative approach to measure events that have occurred. Through structural model analysis (SEM) of lecturers from several culinary arts vocational education institutions in Yogyakarta-Central Java Province. The results of the study indicate that transformational leadership and partnership management have a positive and significant influence on graduate quality assurance. Joint commitment is also proven to act as a mediator that strengthens the relationship between transformational leadership and partnership management with graduate quality assurance. These findings provide theoretical and practical contributions to the development of strategies for improving the quality of graduates in culinary arts vocational education, as well as offering guidance for educational institutions and other related parties in implementing transformational leadership, building strong partnerships with industry, and ensuring joint commitment from all stakeholders. In conclusion, the quality assurance of graduates in the culinary arts field is greatly influenced by the level of shared commitment among all stakeholders, including educational institutions, teachers, and industry. The implication is that educational institutions need to build and strengthen synergistic cooperation and continuous communication with all stakeholders in order to create graduates who are not only technically competent, but also ready to face the demands of the world of work.